2004
DOI: 10.1016/s1526-6125(04)70063-8
|View full text |Cite
|
Sign up to set email alerts
|

Machining, Assembly, and Characterization of a Mesoscale Double Shell Target

Abstract: Several issues related to the manufacture of precision meso-scale assemblies have been identified as part of an effort to fabricate an assembly consisting of machined polymer hemispherical shells and machined aerogel. The assembly, a double shell laser target, is composed of concentric spherical layers that were machined on a lathe and then assembled. This production effort revealed several meso-scale manufacturing techniques that worked well, such as the machining of aerogel with cutting tools to form low den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These hemispherical components mated at a step joint, which incorporated a gap that was partially filled with adhesive. Previous experience fabricating double shell targets revealed that if the ablator hemispherical shells are machined to their finished form as freestanding parts prior to assembling the targets, then it is difficult to bond them properly without getting adhesive on the exterior surface [9]. A cleaner and more precise exterior ablator surface can be obtained by assembling and bonding the target prior to machining the exterior surface of the ablator shell [2].…”
Section: Ablator Shell Componentsmentioning
confidence: 99%
“…These hemispherical components mated at a step joint, which incorporated a gap that was partially filled with adhesive. Previous experience fabricating double shell targets revealed that if the ablator hemispherical shells are machined to their finished form as freestanding parts prior to assembling the targets, then it is difficult to bond them properly without getting adhesive on the exterior surface [9]. A cleaner and more precise exterior ablator surface can be obtained by assembling and bonding the target prior to machining the exterior surface of the ablator shell [2].…”
Section: Ablator Shell Componentsmentioning
confidence: 99%
“…The B-axis is a rotary table mounted on top of the z-axis and rotates the tool in the xz-plane so that it can swivel with respect to the workpiece. The B-axis of the machine tool is used when machining parts with a complex shape, such as aspheres or oddly shaped lenses, and it is a crucial element to machining parts with both interior and exterior features, such as components for a double shell target [1]. Machining components with sub-m accuracy on a four-axis lathe is not a trivial task, and there are several approaches that could be used to achieve the required accuracy.…”
Section: Introductionmentioning
confidence: 99%